Assessment of the Quantitative and Qualitative Residual Effect in Wax Frames Treated with Nano-Neem Extract - Mahmoud Faris Younis Al-Jubouri; Mohammed Y. Sayed Ghani; Arqam Alomari (Journal of Business Economics and Agribusiness, 2025)
The study aims to investigate the residual effect of silver nanoparticles synthesized from neem (Azadirachta indica), by evaluating the ability of honey bees to remove these compounds through their hygienic behavior in wax frames treated with the nano-extract. The application of silver nanoparticles in combination with neem seed extract enhances biological efficacy while reducing environmental impact, thus opening prospects for developing safe and sustainable control strategies. Quantitative and qualitative identification of the nano-compounds were performed by using several analytical instruments, including: Fourier Transform Infrared Spectroscopy (FT-IR) to detect functional groups, Gas Chromatography–Mass Spectrometry (GC-MS) to identify bioactive nano-compounds, and Atomic Absorption Spectrophotometer (AAS) to determine the quantitative concentration of silver nanoparticles. The results were showed that the concentration of silver in the neem nano-extract was 136.7 ppm before exposure to cleaning, while it significantly decreased in the wax frames treated with the nano-extract to 0.3 ppm after being cleaned by worker bees. In our conclusion is considered low and safe, as it falls within acceptable limits for human health